A density functional theory study of the mechanisms of oxidation of ethylene by rhenium oxide complexes† - Aniagyei, Albert; Tia, Richard; Adei, Evans (Elsevier, 2020)
An article published by Elsevier and also available at DOI: 10.1039/c3dt50539a